Extracellular HMGB1 Impairs Macrophage-Mediated Efferocytosis by Suppressing the Rab43-Controlled Cell Surface Transport of CD91 - Wang, Yao; Zhang, Wen; Xu, Yu; Wu, Di; Gao, Zhan; Zhou, Jianchun; Qian, Hang; He, Binfeng; Wang, Guansong (Frontiers in Immunology, 2022)
High-mobility group box 1 (HMGB1) protein can impair phagocyte function by suppressing the macrophage-mediated clearance of apoptotic cells (ACs), thereby delaying inflammation resolution in the lungs and allowing the progression of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). However, the precise mechanism underlying this HMGB1-mediated inhibition of efferocytosis remains unknown. The aim of this study was to determine the effect of HMGB1 on macrophage-mediated efferocytosis. We discovered that HMGB1 prevented efferocytosis by bone marrow-derived macrophages (BMDMs) and suppressed the expression of Ras-related GTP-binding protein 43 (Rab43), a member of the Ras-associated binding (Rab) family. The downregulation of Rab43 expression resulted in impaired clearance of apoptotic thymocytes by BMDMs. Subsequent analysis of HMGB1-treated and Rab43-deficient BMDMs revealed the inhibited transport of cluster of differentiation 91 (CD91), a phagocyte recognition receptor, from the cytoplasm to the cell surface. Notably, Rab43 directly interacted with CD91 to mediate its intercellular trafficking. Furthermore, Rab43 knockout delayed the inflammation resolution and aggravated the lung tissue damage in mice with ALI. Therefore, our results provide evidence that HMGB1 impairs macrophage-mediated efferocytosis and delays inflammation resolution by suppressing the Rab43-regulated anterograde transport of CD91, suggesting that the restoration of Rab43 levels is a promising strategy for attenuating ALI and ARDS in humans.